(untitled) (Tanzania Medical Journal, 2016)
Tanzanian medical community witnessed the first ever neuroradiology conference, which was held in June 12th to 13th, 2015 and brought together local and international experts on the radiology and imaging.The Organising Committee of the First Tanzania Neuroradiology Conference wishes to express their sincere appreciations to everyone who participated actively to make the Conference a success.First the Committee feels indebted to the two organisations which accepted the idea of co-organising the Conference, that is the Muhimbili University of Health and Allied Sciences (MUHAS) through the Directorate of Continuous Education and the School of medicine through the Department of Radiology and Imaging, and the Medical Radiology and Imaging Professionals Council (MRIPC) of the Ministry of Health and Social Welfare (MOHSW). These two Institutions provided logistical and academic guidance towards organizing the academic based conference and awarded the participants the Credit points.The Committee wishes to take this opportunity to express our sincere thanks to sponsors of this Conference, who made it possible for us to have this forum here at this prestigious hotel. They are mentioned below and their logos will be attached as annex to these proceedings. Special thanks to our main sponsor –KOFIH and the Ministry of Health and Welfare of the Republic of South Korea who provided generously to this Conference and to them we say kamsamnida. We would also wish to thank you all the participants who attended this Conference, the presenters and especially the presenters from Abroad, including the UK, USA, South Korea, Kenya and Uganda. Your participation was of great contribution to our nation and the profession as a whole. We say it again thank you and please be ready to contribute and participate next time.Lastly but not the list is the management of the Protea Courtyard Hotel, who accepted us in their premises and were prompt whenever we needed their assistance. We know we may have been very demanding, but all was in the spirit of making a Conference successful. Please accept our apologies where we did not go congruent, but accept our appreciation for the wonderful hosting we got.Details of the current publications can be accessed at the Tanzania Medical Journal, under special issue Volume 28, No. 1: download full issue at: http://tmj.or.tz/pdf/special.pdfOrganising committeeMarch 2016